2015
DOI: 10.1001/jamaoto.2015.1463
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Functional Outcomes of Total Glossectomy With or Without Total Laryngectomy

Abstract: In patients with total glossectomy, feeding tube dependence was not associated with laryngeal preservation or the reconstructive technique, including flap innervation and type of flap used. Laryngeal preservation was associated with favorable speech outcomes such as the retained ability to verbally communicate and higher levels of speech intelligibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
1
41
1
2
Order By: Relevance
“…Concomitant total laryngectomy eliminates the risk of postoperative aspiration as well as provides for more aggressive cancer control for base of tongue cancers extending toward or involving the supraglottis. Furthermore, recent findings showed that laryngeal preservation in total glossectomy is not associated with more feeding‐tube dependence and provides superior long‐term speech outcomes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant total laryngectomy eliminates the risk of postoperative aspiration as well as provides for more aggressive cancer control for base of tongue cancers extending toward or involving the supraglottis. Furthermore, recent findings showed that laryngeal preservation in total glossectomy is not associated with more feeding‐tube dependence and provides superior long‐term speech outcomes …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent findings showed that laryngeal preservation in total glossectomy is not associated with more feeding-tube dependence and provides superior long-term speech outcomes. 10 We reviewed patient and clinicopathologic characteristics and both oncologic and reconstructive outcomes of those who received total glossectomy with free flap reconstruction at our institution. In this study, the patient demographics, clinical and pathologic information, treatment and reconstructive outcomes, and quality-of-life (QOL) outcomes were analyzed and reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…The planned introduction of voice banking in our region may further improve this experience. In other series, Gehanno et al reported no patients, Sinclair et al reported 10%, and Lin et al 44% of patients achieving speech. By comparison, patients receiving a total glossectomy alone have higher reported rates of functional speech (30%‐97%) …”
Section: Discussionmentioning
confidence: 90%
“…Sinclair et al reported that 20% of their total glossolaryngectomy patients achieved tube‐free oral feeding; feeding tube dependence was significantly higher in their total glossectomy cohort. In contrast, Lin et al in their cohort of 17 glossolaryngectomy and 38 glossectomy patients, reported 45% achieved tube‐free feeding, with no significant difference between the cohorts.…”
Section: Discussionmentioning
confidence: 90%
“…These results can be explained by the finding that pectoralis flaps were used more often when concurrent total laryngectomy was performed. No difference was noted in swallowing when comparing pectoralis flaps with free tissue reconstructions [19].…”
Section: Stenosismentioning
confidence: 86%